Kontribusi Intrapersonal Skills dan Interpersonal Skills Terhadap Kesiapan Kerja Pada Mahasiswa Perguruan Tinggi “X” - entot suhartono; zaky machmuddah (Universitas Serang Raya, 2020)
The low quality of human resources in Indonesia is evidenced by the high level of unemployment in Indonesia. Data from the Central Statistics Agency show that open unemployment in Indonesia at the last high school level was 1.93 million, at the vocational level at 1.73 million, at the Diploma level at 220,932 and at the Bachelor level at 729,601 (BPS, 2018) . This phenomenon illustrates that labor readiness is still low in Indonesia. Higher education plays an important role to improve this. Producing graduates who are superior, skilled and have full competence in themselves is the main goal of every college. Empirically proving the relationship between intrapersonal skills and interpersonal skills to work readiness in